Culture-Centered Processes of Community Organizing in COVID-19 Response: Notes From Kerala and Aotearoa New Zealand - Dutta, Mohan J.; Elers, Christine; Jayan, Pooja (Frontiers in Communication, 2020)
The culture-centered approach (CCA) foregrounds the organizing role of communities at the "margins of the margins" of the globe as the spaces for identifying the structural challenges to health and wellbeing and for co-creating community-anchored solutions to these challenges. Pandemics such as COVID19 render visible the deep-rooted inequalities across and within societies, seeded and catalysed by over three decades of variegated neoliberal reforms (Dutta, 2016). The trajectories of COVID19 outbreaks as well as the effects of COVID19-related policies render visible the inequalities that are written into the neoliberal organizing of political economy. Community participation is scripted into the neoliberal framework as an instrument for depoliticizing community and utilizing it as a channel for disseminating top-down indivdiual behavior change messages. Drawing on the examples of community organizing in Kerala where the Communist Party of India (Marxist) has actively co-created an infrastructure for socialist organizing, and iwi-led Maori checkpoints in Aotearoa New Zealand, we delineate the features of transformative community organizing. Community organizing in the CCA is political, foregrounding community sovereignty as the basis for resisting neoliberal health structures. Community struggles for communication equality thus point to alternative forms of organizing health and wellbeing that challenge and seek to dismantle neoliberal governmentality.